Endotracheal tubes coated with a broad-spectrum antibacterial ceragenin reduce bacterial biofilm in an in vitro bench top model. (5th February 2021) - Latorre, María Consuelo; Pérez-Granda, María Jesús; Savage, Paul B; Alonso, Beatriz; Martín-Rabadán, Pablo; Samaniego, Rafael; Bouza, Emilio; Muñoz, Patricia; Guembe, María
Abstract: Background: Ventilator-associated pneumonia is one of the most common nosocomial infections, caused mainly by bacterial/fungal biofilm. Therefore, it is necessary to develop preventive strategies to avoid biofilm formation based on new compounds. Objectives: We performed an in vitro study to compare the efficacy of endotracheal tubes (ETTs) coated with the ceragenin CSA-131 and that of uncoated ETTs against the biofilm of clinical strains of Pseudomonas aeruginosa (PA), Escherichia coli (EC) and Staphylococcus aureus (SA). Methods: We applied an in vitro bench top model using coated and uncoated ETTs that were treated with three different clinical strains of PA, EC and SA for 5 days. After exposure to biofilm, ETTs were analysed for cfu count by culture of sonicate and total number of cells by confocal laser scanning microscopy. Results: The median (IQR) cfu/mL counts of PA, EC and SA in coated and uncoated ETTs were, respectively, as follows: 1.00 × 10 1 (0.0–3.3 × 10 2 ) versus 3.32 × 10 9 (6.6 × 10 8 –3.8 × 10 9 ), P <  0.001; 0.0 (0.0–5.4 × 10 3 ) versus 1.32 × 10 6 (2.3 × 10 3 –5.0 × 10 7 ), P <  0.001; and 8.1 × 10 5 (8.5 × 10 1 –1.4 × 10 9 ) versus 2.7 × 10 8 (8.6 × 10 6 –1.6 × 10 11 ), P =  0.058. The median (IQR) total number of cells of PA, EC and SA in coated and non-coated ETTs were, respectively, as follows: 11.0 [5.5–not applicable (NA)] versus 87.9 (60.5–NA), P =  0.05; 9.1 (6.7–NA) versus 62.6 (42.0–NA), P  =   0.05; and 97.7 (94.6–NA) versus 187.3 (43.9–NA), P =  0.827. Conclusions: We demonstrated significantly reduced biofilm formation in coated ETTs. However, the difference for SA was not statistically significant. Future clinical studies are needed to support our findings.